2021
DOI: 10.2147/ijn.s325625
|View full text |Cite
|
Sign up to set email alerts
|

Formulation, Optimization, and Evaluation of Oregano Oil Nanoemulsions for the Treatment of Infections Due to Oral Microbiota

Abstract: Introduction Natural oil-based nanoemulsions (NEs) have been widely investigated in many diseases that affect the oral cavity. NEs are delivery systems that enhance the solubility of lipid therapeutics and improve their delivery to target sites; they are known as self-nanoemulsifying drug delivery systems (SNEDDSs). The current investigation’s aim was to produce an oregano essential oil-based nanoemulsion (OEO-SNEDD) that would have antibacterial and antifungal effects against oral microbiota and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 52 publications
3
29
0
Order By: Relevance
“…After these cycles, the final samples were analyzed for droplet size. The samples’ stability indexes were determined by comparing the obtained droplet size with that in initial measurements, using the following equation [ 31 ]: …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After these cycles, the final samples were analyzed for droplet size. The samples’ stability indexes were determined by comparing the obtained droplet size with that in initial measurements, using the following equation [ 31 ]: …”
Section: Methodsmentioning
confidence: 99%
“…enzymatic degradation, (3) promoting drug loading, solubility, and pharmacokinetic features, (4) diminishing interpatient and intrapatient variations, and (5) controlling the release of studied drugs [30,31].…”
Section: Estimation Of LV Solubility In Various Snedds Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the antifungal activity evaluation, it was observed that the inhibition area was correlated with the increase in oil and surfactant content. Maximum antifungal activity was predicted when oregano oil was settled at 18% and the surfactant mixture of Pluracare and Lauroglyocl FCC (1.25:1) was settled at 36% [ 149 ]. Thymol and carvacrol are phenolic components of the essential oil, responsible for enzymatic degradation in the fungi structure.…”
Section: Biomaterials and Nanotechnological Approachesmentioning
confidence: 99%
“…Self-nanoemulsifying drug delivery systems (SNEDDS) using bioactive lipid compounds have recently attracted attention as delivery systems to provide synergistic benefits and improve the oral bioavailability and/or biological activity of lipophilic drugs [25][26][27][28]. The demand for natural formulation active/inactive ingredients has emerged due to the increased risk of side effects posed by the synthetic compounds.…”
Section: Introductionmentioning
confidence: 99%